Analisa Hidrolis Sistem Irigasi Pertanian - Jonri Lomi Ga; Alexius Leonardo Johanis; Jody Alfred Zacharias; Sulche Ifone Nafi; Ferdinand Nikson Liem; Almido Haryanto Ginting (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
The objective of research is to assess the uniformity of pressure and the effectiveness of water distribution among the irrigation nodes. The study models drip and sprinkler irrigation networks in an 11,500 m² agricultural field using a hydraulic modeling technique using EPANET 2.2 software. The number of non-flow nodes in each simulated area, the minimum-maximum discharge, and the average pressure are the primary parameters that are examined. The findings demonstrate that branch diameter, pipe length, and pipe network layout all have a substantial impact on flow rate and pressure distribution. While locations with longer pipe segments encounter pressure drops of up to 5–7 mH₂O at the downstream portion, areas with homogeneous pressure (8–10 mH₂O) demonstrate more steady and effective water distribution performance. It was discovered that the main causes of system efficiency reduction were frictional energy losses and small losses. To increase pressure uniformity, pump energy efficiency, and overall irrigation system reliability, technical suggestions are made to install pressure regulator valves (PRV), optimize pipe diameter, and conduct zoning operations.